Green Fiscal Policy and Sustainable Economic Growth: Evidence from Emerging Markets - Sabiq Syahid Muslim (Review of Human Resources, Organizational Change, and Economic Impact, 2025)
This study examines the role of green fiscal policy in promoting sustainable economic growth in emerging markets. By analyzing various fiscal instruments such as carbon taxes, renewable energy subsidies, and emissions trading schemes, this research assesses their impact on economic performance, environmental sustainability, and investment in green technologies. The findings indicate that well-implemented fiscal policies can significantly contribute to reducing carbon emissions while fostering economic stability and innovation. However, challenges such as regulatory inconsistencies, infrastructural limitations, and industry adaptation remain key hurdles. Addressing these challenges is essential to maximizing the effectiveness of green fiscal measures. Future research should focus on long-term policy impacts, sector-specific adaptations, and international cooperation to enhance green fiscal strategies.